A Public-Private Partnership to Develop Agrivoltaics in the US Midwest - Matthew O'Neal; Nick Petersen; Liang Dong; Hongli Feng; Anne Kimber; Raymond Klein; Ajay Nair; Suzanne Slack; John Tyndall; Hugo Villegas (AgriVoltaics Conference Proceedings, 2025)
The expansion of solar energy at a utility scale in the Midwest of the USA will include land currently being used for farming.  This development does not have to remove this land from agricultural use, if agrivoltaic practices are considered.  However, there is a lack of data and recommendations for how solar facilities can be used for agricultural purposes. To address this gap, Iowa State University (ISU) and Alliant Energy have entered into a public-private partnership to explore the agronomic, economic and social aspects of agrivoltaic practices. This partnership models future interactions between landowner and utility companies interested in siting solar farms on land currently used for agricultural purposes. In this presentation, we describe how this partnership was developed and led to the construction of a solar farm that can measure both the value of crop production and the impact of understory vegetation on energy production. Through a series of meetings with Alliant Energy representatives and faculty at ISU, a site design was implemented, officially titled the Alliant Energy Solar Farm at Iowa State University. We summarize preliminary results from our initial field season, noting how a common vegetable crop, summer squash, was produced and responded to the conditions at this solar farm.